A Wavelet Transform Based Study on the Representativeness of Preselected Frequency Points of the Insertion Loss Function in Fuzzy Performance Evaluation of Access Network Links - Lilik, F.; Nagy, S.; Kóczy, L. T. (Acta Technica Jaurinensis, 2015)
The performance evaluation of telecommunication networks and connections is a usual problem of telecommunications service providers and network owners. The performance evaluation in our previous approach is strongly (but not exclusively) based on the insertion loss values of the wire pairs measured at certain discrete frequency points. According to experimental results, the usage of these frequencies leads to correct evaluation, however, the theoretic verification of the correctness of the placement of these points seems to be necessary. The study was carried out using wavelet analysis, comparing the insertion loss values measured at the discrete frequency points with the wavelet transformed sections of the insertion loss functions corresponding to them. In this paper, using wavelet transform, we have studied whether the previously selected characteristic frequencies represent well the frequency domain around them also rules using wavelet transformed data are compared to the rules of the method based on characteristic frequencies.